Alterações faciais decorrentes do tratamento da má oclusão de classe III, com deficiência de maxila, empregando disjunção maxilar e tração reversa - Antoniazzi, Simone Pippi (2011)
Introduction: Treatment with Rapid Maxillary Expansion (RME) and Facemask Therapy (FM) has been reported as one of the most effective forms of treatment for patients with Class III malocclusion, with maxillary involvement. Objective: To evaluate the cephalometric changes in the facial tegumentary in patients with malocclusion of skeletal Class III with maxillary retrusion, with greater or less extent, immediately after orthopaedic therapy, with RME/FM. Methods: The treatments with RME/FM were performed by a single operator in a suitably selected sample (10 girls and 6 boys), whose the initial and final data were collected on two times (T0 and T1), evaluating cephalometric parameters and soft tissue. The experimental phase lasted about 12 months. The data were analyzed and compared statistically (Wilcoxon Test - SPSS 13.0), through descriptive analysis, on changes in facial tissue and bone, and dental conditions. Results: A significant increase in maxillary forward growth, inhibition of mandibular forward growth, and clockwise rotation of the mandible were observed. The maxillary incisors were significantly proclined and the mandibular incisors significantly retroclined. Conclusion: Changes produced in the midface were clinically and cephalometric observed, demonstrating anterior displacement of maxilla and point "A", improvement in facial convexity, correction of the anterior crossbite, increase in the overbite and overjet. However, more studies are needed, since the information in the literature are still inconclusive, given the divergent findings and consensus between authors.